2017
DOI: 10.1159/000453360
|View full text |Cite
|
Sign up to set email alerts
|

Uveal Melanoma Cell Seeding after Transretinal Tumor Biopsy

Abstract: Background/Aims: To report a case and the histopathology of uveal melanoma cell seeding following transretinal tumor biopsy for a suspected uveal lesion. Methods: Interventional case report. Results: A 66-year-old male presented with a pigmented perilimbal episcleral lesion overlying an intraocular mass at the pars plana, 3.5 years after transretinal biopsy and ruthenium plaque brachytherapy for a choroidal melanoma at the posterior pole. The patient underwent enucleation of the eye. Histopathology confirmed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Furthermore, the scleral ports likely reduce the risk of tumor seeding in the sclera [27]. However, the risk of scleral seeding is not entirely eliminated, as demonstrated by case reports of extraocular recurrence at the scleral port entry site following a transvitreal biopsy [47,48]. The vitrector system allows for sufficient biopsy material with a single pass compared to transscleral biopsies, which usually demand several passes, increasing the number of seeded tumor cells mainly if multiple needle tracts are performed [41].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the scleral ports likely reduce the risk of tumor seeding in the sclera [27]. However, the risk of scleral seeding is not entirely eliminated, as demonstrated by case reports of extraocular recurrence at the scleral port entry site following a transvitreal biopsy [47,48]. The vitrector system allows for sufficient biopsy material with a single pass compared to transscleral biopsies, which usually demand several passes, increasing the number of seeded tumor cells mainly if multiple needle tracts are performed [41].…”
Section: Resultsmentioning
confidence: 99%
“…[56] However, the risk of scleral spread is not completely eliminated, as demonstrated by case reports of extraocular recurrence at the scleral port entry site after transvitreous biopsy. [63,64] e vitrectomy system allows sufficient biopsy material to be obtained with a single pass compared to trans-scleral biopsies, which usually require several passes, increasing the number of tumor cells seeded mainly if multiple needle trajectories are performed. [16] Nevertheless, UM FNA is generally accepted as a safe procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, several studies proved the safety of FNAB for choroidal melanoma with the transscleral or pars plana transvitreal approach, [1][2][3] and cases of extraocular extension are rare. [4][5][6][7] Schefler et al [4] reported extraocular extension in four patients with uveal melanoma, but three of them had undergone vitrectomy and/or open biopsy in addition to FNAB. The interval between FNAB and the detection of extraocular extension in their series ranged from five months to approximately nine years.…”
Section: Discussionmentioning
confidence: 99%
“…Mashayekhi et al [6] reported one patient with extraocular extension of ciliochoroidal melanoma one and a half years after transscleral FNAB using a 25-gaugeneedle without infusion. Koch et al [7] reported pars plana seeding with localized extraocular extension 3.5 years after transretinal biopsy of choroidal melanoma using a 25-gauge vitrectomy probe followed by Ruthenium-106 plaque radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation